The study of short-term efficacy of intralesional injection of combination of triamcinalone, hyaluronidase and mitomycin in Peyronies disease - S., Raghupathi; ., Raghavendra (International Surgery Journal, 2018)
Background: Peyronies disease (PD) is physiologically and psychologically devastating disorder that is manifest by a fibrous inelastic scar of tunica albugenia resulting in palpable penile scar and deformity. Different modalities of nonsurgical treatment options exist without promising results in the long-term improvements of symptoms. The injection of pharmacologically active agents directly in to the penile plaque results in localized delivery and higher drug concentrations inside the plaque. With this rationale the study is planned to analyze the effectiveness of intralesional injection of triamcinalone, hyaluronidase, and mitomycin in the treatment of PD. Methods: Patients with symptomatic PD presenting at PGIMER from 1st July 2013 to 30th September 2014 were included in the study after obtaining the informed consent. A freshly prepared solution of a mixture of Triamcinalone, Hyaluronidase and Mitomycin was injected at the periphery as well as in the plaque. The patients were followed up for every four weeks for three months for the improvement of symptoms. Results: A total of 21 patients of symptomatic Peyronies disease with mean age of 44.4 and mean duration of 5.6 months were treated and followed up at PGIMER during July 2012 to September 30th, 2014. After completion of 3 months of treatment, 15/21 patients showed improvement in penile curvature. The overall response rate was 71.4% (p=0.001). 14/21 patients showed improvement in plaque size. The overall response rate was 66.66 (p=0.036). The IIEF-15 and PROSB score improved significantly both at 1st and 3rd month of follow up from the baseline score. Conclusions: This pilot study showed that the intralesional injection therapy is safe, well tolerated and effective in reducing the plaque size, penile curvature, and erectile dysfunction and patient’s bothersome score.